INFLUENCE OF USE OF MEDIA NUMBER CONCEPT TUNANETRA ABILITY TO READ BRAILLE NUMBERS - Prita Nuraeni; Dr. Hj. Isti Rusdiyani, M.Pd; Ratih Listiyaningtyas, M.Pd (UNIK (Jurnal Ilmiah Pendidikan Luar Biasa), 2018)
Abstract Children with visual impairments have difficulty reading, also have difficulty recognizing numbers. Media The concept of numbers is a medium used to help learning about the concept of numbers for blind children. The purpose of this study was to obtain data and information about the effect of using the concept of numerical numbers on the ability to read Braille numbers in second grade elementary school students at Garut State SLN. The method used in this study is the experimental method using the Single Subject Research (SSR) approach, while the design used is the A-B-A design. there are three target behaviors in this study, namely 1) the ability to say numbers verbally, 2) the ability to show numerical symbols with beams, and 3) the ability to read Braille numbers. The data obtained was analyzed through descriptive statistics, and displayed through graphs. Based on the results of the study, it is known that the use of media concept numbers increases the ability to read Braille numbers in blind children. This is indicated by the increase in the mean in the three target behaviors.